1990
DOI: 10.1093/ajcn/51.6.1020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of shellfish consumption on lipoproteins in normolipidemic men

Abstract: Eighteen normolipidemic males were fed six different species of shellfish; each shellfish was fed so that protein in shellfish equalled that in animal foods in the normal diet, with less than one-half of the amount of fat in animal foods allowed for preparation of the shellfish. Oyster, clam, crab, and mussel diets, low in cholesterol and high in n-3 fatty acids, lowered VLDL triglycerides and cholesterol and, except for the mussel diet, LDL and total cholesterol. Squid and shrimp diets, higher in cholesterol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 24 publications
0
14
0
2
Order By: Relevance
“…Thus for the majority of the population, PCB TEQ from fish is probably not a driving contributor of dioxin-like risk. This is an important finding since there are many reasons to promote consumption of fish and seafood including health benefits such their value as low fat high protein foods and reducing risk of heart disease (Childs et al, 1990;Uauy and Valenzuela, 2000). Previous studies evaluating potential health risks from carcinogenic contaminants in fish (including dioxin and PCBs) have also indicated that the health benefits of consuming many species of fish outweigh the potential risks (Sidhu, 2003).…”
Section: Exposures For Average and High-level Consumersmentioning
confidence: 92%
“…Thus for the majority of the population, PCB TEQ from fish is probably not a driving contributor of dioxin-like risk. This is an important finding since there are many reasons to promote consumption of fish and seafood including health benefits such their value as low fat high protein foods and reducing risk of heart disease (Childs et al, 1990;Uauy and Valenzuela, 2000). Previous studies evaluating potential health risks from carcinogenic contaminants in fish (including dioxin and PCBs) have also indicated that the health benefits of consuming many species of fish outweigh the potential risks (Sidhu, 2003).…”
Section: Exposures For Average and High-level Consumersmentioning
confidence: 92%
“…O total de ácidos graxos 20:5 e 20:6 das ostras analisadas (30%) foi inferior às analisadas por Knauer e Southgate (1997) com 50%, semelhante às de Childs et al (1990) com 32% e superiores as de Tanaka et al (2003) com apenas 20%, em ostras da mesma espécie. Abad et al (1995) e Soudant et al (1999 observaram que os ácidos graxos com maior variação sazonal nas ostras são os ácidos graxos da série ômega-3, sendo estes dependentes do tipo e quantidade de alimentos e do ciclo reprodutivo.…”
Section: Resultsunclassified
“…Assim como no presente estudo, os ácidos graxos 16:0, 18:1, 20:5 (EPA) e 22:6 (DHA) foram predominantes como saturado, monoinsaturados e poli-insaturados, respectivamente, para ostras cultivadas em diferentes regiões (CHILDS et al, 1990;LINEHAN;O'CONNOR;BURNELL, 1999;MARTINO;CRUZ, 2004). Pernet et al (2007) …”
Section: Introductionunclassified
“…Childs et al, re ported that oysters are hypolipidemic in normolipi demic men (4). The hypocholesterolemic effect of oys tern is in part attributed to non-cholesterol sterols such as sitosterol and brassicasterol.…”
Section: (Received August 29 2002) Summarymentioning
confidence: 99%